Dinamika Survival Petani dan Tantangan De-agrarianisasi - Christine E. Meka; Hildigardis M.I. Nahak (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2022)
In the midst of agricultural infrastructure development projects that are massively promoted by the state, the portrait of farmers often stagnates, even declines in local economic networks. The aim of this research is to present the dynamics of the relationship between farmers and land in West Timor, East Nusa Tenggara. The method of this research is descriptive-qualitative through indepth interview and observation. By using an agrarian political economy perspective, this paper finds several things, i.e 1) the position of farmers is not completely dependent on agriculture. Their main occupation as farmers does not make them independent farmers in the agricultural sector. 2) Farmers carry out other activities, especially animal husbandry. This business actually generates income that is much greater than agricultural production in order to help them survive. 3) The disposition of smallholders seems very vulnerable to systemic impoverishment, meanwhile, farmers who own rice fields can still get capital accumulation from agricultural businesses. In the end, the struggle of the farmers in Timor was carried out in order to survive in the midst of economic difficulties due to the free market which then created the challenge of de-agrarianization.